1983
DOI: 10.1126/science.6407107
|View full text |Cite
|
Sign up to set email alerts
|

Increased Chromosomal Mutation Rate After Hybridization Between Two Subspecies of Grasshoppers

Abstract: Hybridization between two chromosomally distinct subspecies of the grasshopper Caledia captiva results in a high incidence of novel chromosomal rearrangements among the backcross progeny. Rearrangements are restricted to those chromosomes derived from the F1 hybrid parent. Chromosomal involvement is nonrandom with the same rearrangement occurring repeatedly in different backcrosses. A single individual can also generate an array of different rearrangements among its offspring. Several of the rearrangements hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…One consequence of the intraspecific release of mutator activity is that high levels of rare genetic variants observed in hybrid zones (Hunt and Selander, 1973;Avise and Smith, 1974;Kilpatrick and Zimmerman, 1976;Gould and Woodruff, 1978;Sage and Selander, 1979;Smith, 1979;Moran et a!., 1980;Greenbaum, 1981;Hafner, 1982;Peters, 1982;Barton et aL, 1983) may be due to increased rates of mutation (Woodruff et aL, 1979;Thompson and Woodruff, 1980), although intragenic recombination could also explain these variants (Golding and Strobeck, 1983). Support for increased rates of mutation as the cause of the increased genetic variation in hybrid zones comes from the observation that high frequencies of novel chromosome re-arrangements are observed in hybrid zones of grasshoppers and the re-arrangements are derived only from hybrid parents (Shaw et aL, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One consequence of the intraspecific release of mutator activity is that high levels of rare genetic variants observed in hybrid zones (Hunt and Selander, 1973;Avise and Smith, 1974;Kilpatrick and Zimmerman, 1976;Gould and Woodruff, 1978;Sage and Selander, 1979;Smith, 1979;Moran et a!., 1980;Greenbaum, 1981;Hafner, 1982;Peters, 1982;Barton et aL, 1983) may be due to increased rates of mutation (Woodruff et aL, 1979;Thompson and Woodruff, 1980), although intragenic recombination could also explain these variants (Golding and Strobeck, 1983). Support for increased rates of mutation as the cause of the increased genetic variation in hybrid zones comes from the observation that high frequencies of novel chromosome re-arrangements are observed in hybrid zones of grasshoppers and the re-arrangements are derived only from hybrid parents (Shaw et aL, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hybridisation among migrants in the large-density winery population might be expected to increase mutation rates by the documented intraspecific hybrid release of mutator activity (Thompson and Woodruff, 1980;Woodruff et a!., 1980;Shaw et a!., 1983). As an indication of the possible impact of hybrid release on the rate of genetic change in nature, Woodruff and Thompson (1982b, and in preparation) have observed that the progeny from 25 of 90 crosses between natural population lines of D. melanogaster have a significantly higher frequency of spontaneous lethal mutations than do the base populations, and similar values have been observed for spontaneous breakage in hybrid progeny.…”
Section: Discussionmentioning
confidence: 99%
“…As this phenomenon appears to extend to other organisms (cf. Shaw et al, 1983) and to mutations of small effects (Mackay, 1984), it is feasible that the evolution of parthenogenesis may be accompanied by a rise in VM at least early in its transitional stages.…”
Section: Discussionmentioning
confidence: 99%
“…At the narrowest zone (3), no male chromosomal heterozygotes were found. (2) Hybridization might result in an increased chromosomal mutation rate, which could disguise heterozygous weta and reduce the estimates of cline width (Shaw et al 1983;Naveira and Fontdevila 1985;Morgan-Richards 1995). For example, where karyotypes differ in the number of pairs of small autosomes (Zones 1 and 3), duplication of unpaired autosomes in hybrids could produce parental-type karyotypes.…”
Section: Variation In Chromosome Cline Widths Among Five Zonesmentioning
confidence: 99%